BIRTH CONTROL OF MEDICAL JOURNALS - Habibzadeh, Farrokh (Journal of Postgraduate Medical Institute, 2015)
Medical journals are among the most important means of dissemination of new scientific information across physicians and researchers worldwide. Many clinicians shape their treatment strategies based on evidence-based medicine principles, which in turn, seriously rely on research articles published in these journals. The question arise is how reliable are the results of the published articles in these journals?